Objective criteria for the quality of life of patients who underwent surgery (literature review) - A. Kh. Mnoyan; S. V. Zhukov; A. M. Morozov; A. A. Bagdasarov; E. S. Petrukhina; V. P. Stepanenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. One of the tasks of modern surgery is to provide high-quality medical care with a significant impact on the patient, which should lead to an improvement in the quality of life. Quality of life assessment is becoming increasingly relevant in healthcare and is associated with improved decision-making, higher satisfaction and better treatment outcomes.The purpose of the study. To identify criteria for an objective assessment of the quality of life of patients in the postoperative period.Materials and methods. In the course of this study, the most relevant domestic and foreign literary sources were analyzed, reflecting the problem of assessing the quality of life of patients in the postoperative period.Results. To assess the quality of life, various forms of questionnaires for patients are usually used. Questionnaires can be both general and specific for a particular disease. After analyzing numerous questionnaires to determine the quality of life, it became possible to combine and classify objective criteria for the quality of life.Conclusion. The use of general and special questionnaires makes it possible to perform a full-scale assessment of both the main components of the quality of life and its specific aspects in this disease. At the same time, it is important to take into account the influence of various factors, including gender, age, and the initial quality of life, on the change in indicators over time. This approach is the most correct and corresponds to modern recommendations for analyzing quality of life data that changes over time and is associated with various factors.